2018
DOI: 10.1097/md.0000000000013148
|View full text |Cite
|
Sign up to set email alerts
|

Invasive ACTH-secreting pituitary macroadenoma in remission after transsphenoidal resection

Abstract: Rationale:Knosp grade 4 adrenocorticotropic hormone (ACTH)-secreting pituitary adenoma is a rare cause of Cushing disease. After the 1st surgery, the remission rate among these patients is extremely low.Patient concerns:We presented a case of a 33-year-old female with classical Cushingoid symptoms. Further investigations revealed ATCH-dependent hypercortisolemia, as well as a Knosp grade 4 pituitary macroadenoma.Diagnosis:Cushing disease, caused by a Knosp grade 4 pituitary macroadenoma.Interventions:The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(42 reference statements)
0
6
2
2
Order By: Relevance
“…If the tumor extends into the suprasellar region, a transcranial approach may be needed ( 88 ). In a literature review of initial surgery for ACTHomas, a tumor with Knosp grades 3–4 have been identified in 12–20% of all tumors, and 12 of 36 patients (33.3%) have achieved the remission criteria ( 95 ), indicating that further treatment option is emergently required for these tumors. In Nelson’s syndrome, pituitary surgery is the first-line treatment; however, the complete remission rate depends on whether the pituitary tumor extends to the extrasellar region, similar to an ordinal pituitary tumor ( 96 ).…”
Section: Treatmentmentioning
confidence: 99%
“…If the tumor extends into the suprasellar region, a transcranial approach may be needed ( 88 ). In a literature review of initial surgery for ACTHomas, a tumor with Knosp grades 3–4 have been identified in 12–20% of all tumors, and 12 of 36 patients (33.3%) have achieved the remission criteria ( 95 ), indicating that further treatment option is emergently required for these tumors. In Nelson’s syndrome, pituitary surgery is the first-line treatment; however, the complete remission rate depends on whether the pituitary tumor extends to the extrasellar region, similar to an ordinal pituitary tumor ( 96 ).…”
Section: Treatmentmentioning
confidence: 99%
“…ACTH secreting pituitary adenomas are known to have a lower prognosis when it comes to large size. Generally, for macroadenomas, it ranges from 12.5-71.1% (2) . However, with the inadequate tumour resection in this patient, the expected prognosis is low.…”
Section: Discussionmentioning
confidence: 99%
“…It indirectly affects the body’s carbohydrate, protein, lipid and water-electrolyte balance. It takes part in maintaining the homeostasis of the neuroimmunoendocrine system [ 83 , 84 , 85 , 86 ]. ACTH is a physiological agonist of the melanocortin system, which affects cell proliferation and maintenance of normal cell homeostasis.…”
Section: Hormones With a Potential Nephroprotective Effectmentioning
confidence: 99%